The Legal Duty to Consult and Meaningful Consultation: A Spectrum of Industry Approaches to Aboriginal Consultation in the Athabasca Oilsands ... - Vredenburg, Vanessa (Graduate Studies, 2015)
This thesis presents an in depth analysis of the factors that influence the way in which resource extraction companies in the Athabasca Oilsands region of northern Alberta conduct Aboriginal consultation. The duty to consult arose historically through constitutional foundations, case law, and now is incorporated into regulatory guidance documents. Although the duty to consult has been documented in many different ways throughout history, there is a current shift in consciousness that there is a need to go beyond compliance with legal and regulatory guidance to move towards gaining ‘social compliance’. A review of current literature relating to Aboriginal community and resource extraction company relationships, sustainable development, and gaining a social license show that by going beyond regulatory compliance towards social compliance, a competitive advantage can be gained. Two models were identified to measure the way in which resource extraction companies conducted Aboriginal consultation: the rules model ...